Analysis of Intrapersonal Skills and Interpersonal Skills on the Welfare of Micro Entrepreneurs in the COVID-19 Era - Anggraeni, Tuti; Tarmidi, Dodon T. (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Micro business actors in the era of the covid-19 pandemic are required to rack their brains in order to maintain the continuity of their business. To be able to overcome the problem of the COVID-19 pandemic, superior human resources are needed, namely those who not only have hard skills but are also good at soft skills. The abilities or skills that must be possessed by micro entrepreneurs, such as being able to read market opportunities, not getting bored quickly, being able to work in teamwork, the ability to communicate verbally and write reports well. We can see this ability in Interpersonal Skills and Intrapersonal Skills, it can be an evaluation material, for researchers to help micro entrepreneurs survive in this pandemic. Interpersonal skills are a person's skills in dealing with others while intrapersonal skills are skills in self-regulation that are able to develop maximum performance. The purpose of this study is to be able to see the interpersonal skills and interpersonal skills possessed by micro business actors in the East Bandung area, in order to be able to overcome the economic problems faced during the COVID-19 pandemic, so that based on these skills they can increase the income and welfare of micro entrepreneurs. The results of this study indicate that the Intrapersonal Skills of micro business actors in the East Bandung area can be categorized very well for change management sub-indicators, personal characteristics and have positive reference goals. However, there are still some micro business actors who have not been able to manage time management in terms of having a regular schedule for training and in the field of stress management there are some who have not been able to share if there is a problem with those closest to them. East Bandung area can be categorized as good, such as the ability to motivate, presentation skills, communication skills, the ability to make relationships, and the ability to speak in public. While that must be a concern is the ability to lead / team work.